William L. Taylor papers - Taylor, William L., 1931-2010.
Correspondence, memoranda, printed matter, reports, speeches, writings, testimony, transcripts of interviews, and other material related primarily to civil rights legislation and efforts to defeat the nominations of Robert H. Bork and Clarence Thomas to the U.S. Supreme Court.
Subjects include the Civil Rights Acts of 1990 and 1991, the Lawyers' Committee for Civil Rights Under Law, the Leadership Conference on Civil Rights, the NAACP Legal Defense and Educational Fund, interviews of Taylor conducted by Michael Pertschuk and Wendy Schaetzel (Lesko), affirmative action, civil rights, civil rights organizations, civil rights protections in education and employment, and school desegregation.
Civil rights lawyer and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Material from the records of the Center for National Policy Review which came to the Library in 1993 was later transferred to these papers.
Keywords: Bork, Robert H; Pertschuk, Michael, -- 1933-; Lesko, Wendy; Thomas, Clarence, -- 1948-; United States; United States. -- Congress. -- Senate. -- Committee on the Judiciary; United States. -- Supreme Court; United States. -- Supreme Court -- Officials and employees -- Selection and appointment; Lawyers' Committee for Civil Rights Under Law; Leadership Conference on Civil Rights; NAACP Legal Defense and Educational Fund; Affirmative action programs in education -- United States; African Americans -- Civil rights; Civil rights -- United States; Civil rights -- United States -- Societies, etc; Discrimination in education -- United States; Discrimination in employment -- United States; Judges -- Selection and appointment -- United States; Minorities -- Civil rights -- United States; School integration -- United States; Civil rights leaders; Educators